Functional studies of plant transcription factors and their relevance in the plant root-knot nematode interaction - Domínguez-Figueroa, Jose; Gómez-Rojas, Almudena; Escobar, Carolina (Frontiers in Plant Science, 2024)
Root-knot nematodes are polyphagous parasitic nematodes that cause severe losses in the agriculture worldwide. They enter the root in the elongation zone and subtly migrate to the root meristem where they reach the vascular cylinder and establish a feeding site called gall. Inside the galls they induce a group of transfer cells that serve to nurture them along their parasitic stage, the giant cells. Galls and giant cells develop through a process of post-embryogenic organogenesis that involves manipulating different genetic regulatory networks within the cells, some of them through hijacking some molecular transducers of established plant developmental processes, such as lateral root formation or root regeneration. Galls/giant cells formation involves different mechanisms orchestrated by the nematode´s effectors that generate diverse plant responses in different plant tissues, some of them include sophisticated mechanisms to overcome plant defenses. Yet, the plantnematode interaction is normally accompanied to dramatic transcriptomic changes within the galls and giant cells. It is therefore expected a key regulatory role of plant-transcription factors, coordinating both, the new organogenesis process induced by the RKNs and the plant response against the nematode. Knowing the role of plant-transcription factors participating in this process becomes essential for a clear understanding of the plant-RKNs interaction and provides an opportunity for the future development and design of directed control strategies. In this review, we present the existing knowledge of the TFs with a functional role in the plant-RKN interaction through a comprehensive analysis of current scientific literature and available transcriptomic data.